Analysis of Educational Policy in Madrasah Perspective - Joben, Joben; Asrol, Leyli Desra (JRTI (Jurnal Riset Tindakan Indonesia), 2023)
Madrasah have a strategic role in nation building. Currently madrasa education is still considered a "second class" education. This occurs because of the implementation of the madrasa still faces a number of major issues such as the management problems start and the low quality of madrasah education. This paper is intended to give an overview of the progress madrasah education system in Indonesia, madrasas issues, opportunities and challenges of the madrasa. Madrasas have become part of the national education system. The method used in this study is a literature study by collecting secondary data from various sources of books and journals, then conducting a descriptive analysis of the data presented in detail. Various problems faced by madrasas include the management of education, the gap between public and private, the quality of madrasas,Keywords:Madrasah, Education